An exploration of entrepreneurial ecosystems for biopharma SMEs in a second-tier region: Deploying cognitive proximity as a theoretical lens for ecosystems and relationships - Gonzalez Lopez, Jose Francisco (2022)
Entrepreneurial ecosystems are becoming an important subject area in academia as these regional structures are being adopted by governments as a policy initiative aiming to improve regional entrepreneurship and innovation. The concept of entrepreneurial ecosystems has its roots in systems theory and serves as an ecological metaphor as these are settings in which groups of interconnected actors cooperate to promote and facilitate entrepreneurial activities such as business development and innovation within a specific regional context. Therefore, entrepreneurial ecosystems do not only exist, but they require inputs that can be transformed into outputs through interactions with relevant mediators.